2008
DOI: 10.1088/0264-9381/25/8/085004
|View full text |Cite
|
Sign up to set email alerts
|

Spherical symmetry in f ( R )-gravity

Abstract: Spherical symmetry in f(R)-gravity is discussed in detail considering also the relations to the weak field limit. Exact solutions are obtained for constant Ricci curvature scalar and for Ricci scalar depending on the radial coordinate. In particular, we discuss how to obtain results which can be consistently compared with general relativity giving the well known post-Newtonian and post-Minkowskian limits. Furthermore, we implement a perturbation approach to obtain solutions up to the first order starting from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
146
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(147 citation statements)
references
References 82 publications
1
146
0
Order By: Relevance
“…These results were recently extended to any quadratic theory Lagrangian [33]. Within F(R) gravity, several studies have been performed in recent years such as static and spherically symmetric black holes [26,27,[34][35][36][37][38][39], traversable wormholes [40][41][42][43][44][45] and pure double layer bubbles [46].…”
Section: Introductionmentioning
confidence: 99%
“…These results were recently extended to any quadratic theory Lagrangian [33]. Within F(R) gravity, several studies have been performed in recent years such as static and spherically symmetric black holes [26,27,[34][35][36][37][38][39], traversable wormholes [40][41][42][43][44][45] and pure double layer bubbles [46].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it can be considered how to obtain results consistent with GR assuming the well-known post-Newtonian and post-Minkowskian limits as consistency checks. [9].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was shown that in the absence of scalar field, µ = 0, the solution is recovred by the empty spacetime Schwarzschild solution. Our aim here is to extend and use Buchdahl's solution to find an approximated solution for (14). We take in to the account that the nonlinearity parameter β is smallness parameter and we try to extend the solutions of (14) in a series of perturbations.…”
Section: Slightly Modified Xanthopolous and Zannias Solutionsmentioning
confidence: 99%
“…The case with γ = −1 represents the Schwarzschild solution with negative mass which it has a naked singularity. Our aim here to find the exact solution (black hole) with β = 0 for (14). One possibility is to use perturbation method around this exact solution (β = 0 case) as the following:…”
Section: Slightly Modified Xanthopolous and Zannias Solutionsmentioning
confidence: 99%